Strategi Komunikasi LAZNAS Yatim Mandiri: (Studi Peningkatakan Donatur pada Yatim Mandiri Cabang Surabaya) - Adam Ferdiani Putra Pradana (Al-Maquro\': Jurnal Komunikasi dan Penyiaran Islam, 2021)
The problems studied in this research are: How is the communication strategy carried out by Laznas Yatim Mandiri Surabaya Branch in increasing Dunatur? This study uses a descriptive qualitative method approach. Data collection techniques used are observation, interviews and documentation. The theory used by the researcher is the theory of Symbolic Interaction. The results of the research on the communication strategy of Laznas Yatim Mandiri Surabaya Branch in increasing donors include 1) Approaching and packaging as well as possible the messages that will be conveyed to the community. 2) Provide several programs for orphans and poor people. (3) Holding Major Events for Orphans.